Does counterterrorism militarize foreign aid? Evidence from sub-Saharan Africa. (July 2017) - Heinrich, Tobias; Machain, Carla Martinez; Oestman, Jared
This article studies whether the pursuit of counterterrorism militarizes foreign aid flows. It focuses on the case of US foreign aid to sub-Saharan African states, which recently have experienced an increase in the presence of al-Qaeda or its affiliate terrorist organizations. This article argues that as terrorist groups carry out attacks inside a state's territory, aid towards that state will serve such counterterrorism goals. For one, the state's executive branch will receive increased military aid to immediately fight al-Qaeda or affiliates. For the other, the United States also steps up aid for civil society and development, which could over time undermine al-Qaeda's mobilization and recruitment efforts. In an empirical analysis that covers 46 African states from 1996 to 2011, our results largely corroborate the hypothesized patterns for attacks that occur on a country territory and in the neighborhood. We note, though, that the overall composition of aid shifts relative to the military when there are direct attacks, something that does not occur when attacks happen in the neighborhood only. Our article concludes that concerns about militarization of aid are warranted, but that actual manifestations are nuanced.